Association between chronic disease multimorbidity and leisure-time physical activity: Evidence from the China Multiethnic Cohort study - Li, Yajie; Li, Xianzhi; Yu, Bin; Li, Jingzhong; He, Ruifeng; Nima, Qucuo; Zhou, Junmin (Frontiers in Medicine, 2022)
Objective: To reveal the differences in the associations between multimorbidity and leisure-time physical activity (LTPA) by ethnicities in China. Methods: Self-reported information on a range of occupational, household, transport, and LTPA was collected by interviewer-administered questionnaire. A total of 17 chronic diseases were assessed based on self-reported lifetime diagnoses or medical examinations. Multivariable logistic regression models were used to assess the associations between multimorbidity and the risks of low LTPA. Results: The mean age of all participants was 51.2 years old. Of all, 61.4% were women, and 57.9% were the Han population. A significantly negative association (OR = 0.92, 95% CI = 0.89-0.95) was found between multimorbidity and low LTPA, with a stronger association among minority populations (OR = 0.86, 95% CI = 0.82-0.91) than among the Han population (OR = 0.96, 95% CI = 0.92-1.01). For both the minority population and the Han population, digestive system multimorbidity and digestive-metabolic system multimorbidity had a significantly negative association with low LTPA. For the Han population, the association of intersystem multimorbidity for the circulatory-respiratory system (OR = 1.17, 95% CI = 1.04-1.31) with low LTPA was stronger than that of intrasystem multimorbidity for the circulatory (OR = 1.12, 95% CI = 1.01-1.25) and respiratory systems (OR = 1.14, 95% CI = 1.04-1.25). Conclusions: There are notable ethnic disparities in terms of associations between multimorbidity and low LTPA based on this large multi-ethnic population. Our findings suggest LTPA-tailored interventions should be designed to specific ethnic groups according to different types of multimorbidity.